Angelicin—A Furocoumarin Compound With Vast Biological Potential - Mahendra, Camille Keisha; Tan, Loh Teng Hern; Lee, Wai Leng; Yap, Wei Hsum; Pusparajah, Priyia; Low, Liang Ee; Tang, Siah Ying; Chan, Kok Gan; Lee, Learn Han; Goh, Bey Hing (Frontiers in Pharmacology, 2020)
Angelicin is a member of the furocoumarin group, and currently the lesser known relative of psoralen which is well known for its effectiveness in phototherapy. The furocoumarins as a group have been studied since the 1950s but it is only recently that angelicin has begun to come into its own. It has been the subject of several biological studies and has demonstrated anti-cancer properties against multiple cell lines, exerting effects via both the intrinsic and extrinsic apoptotic pathways, and also demonstrating an ability to inhibit tubulin polymerization to a higher degree than psoralen. Angelicin also demonstrated anti-inflammatory activity in inflammatory related respiratory and neurodegenerative ailments via the activation of NF-κβ pathway. Other bioactivities, such as anti-viral and erythroid differentiating properties of angelicin, were also reported by several researchers with the latter even displaying an even greater aptitude as compared to the commonly prescribed drug, hydroxyurea, which is currently on the market. Apart from that, recently, a new application for angelicin against periodontitis had been studied, where reduction of bone loss was indirectly caused by its anti-microbial properties. Angelicin appears to be a promising compound for further studies especially on its mechanism and application in therapies for a multitude of common and debilitating ailments.